Speech Acts Analysis of Jokowi’s Speech on National Santri Day Commemoration - Rofe’i, Agus; Sulhah, Siti; Heryatun, Yayu; Fitriani, Dini (English Education, Linguistics, and Literature Journal, 2024)
This research deals with the types of illocutionary acts in Jokowi’s opening speech on National Santri Day commemoration. The aim of this research was to analyse the types of illocutionary speech act which was dominantly used in that speech. This research applied descriptive qualitative method and speech act theory by Yule. There were 25 utterances and the percentage of utterances were Representative 44%, Expressive 20%, Directive 20%, Commissive 4%, and Declarative 12%. The result showed that Jokowi states the facts to the audiences about the current existence of santri. It is found that Jokowi’s speech acts in his speech are intended as a statement of fact, description and assertion.